2006
DOI: 10.1002/app.24821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of di(2‐ethyl hexyl)phthalate, by a polymeric plasticizer, on the permeability and leaching properties of poly(vinyl chloride)

Abstract: Acrylonitrile butadiene rubber (NBR) was used as a polymeric plasticizer in poly(vinyl chloride) (PVC) for the partial replacement of di(2-ethyl hexyl)phthalate (DEHP). The effect of this partial replacement on DEHP leaching from the PVC was evaluated at 10, 25, and 408C. The study shows that the incorporation of NBR reduces the rate of DEHP leaching, the reduction being prominent at lower temperatures. Gas permeability of the NBR-modified samples was also evaluated at the above temperatures using oxygen and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In this study, sections of PVC pipe had both ends blocked. [16][17][18][19][20][21][22][23][24][25] Later it was found that the chronic cancer and noncancer effects of DINP on rodent liver are consistent with its known action as a peroxisome proliferator. 13 The amount of UV energy affects the rate of vinyl chloride release and migration.…”
Section: Carcinogenic Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, sections of PVC pipe had both ends blocked. [16][17][18][19][20][21][22][23][24][25] Later it was found that the chronic cancer and noncancer effects of DINP on rodent liver are consistent with its known action as a peroxisome proliferator. 13 The amount of UV energy affects the rate of vinyl chloride release and migration.…”
Section: Carcinogenic Effectmentioning
confidence: 99%
“…14 In addition to their high cancer risks, dioxins adversely affect the immune and endocrine systems and the development of foetuses. 16,17,18,25,26 In the study of DINP it was concluded that soft PVC toys and other children's products do not present a significant risk to children. 14 The dioxins trapped in ash will not affect environment because they are expected to be decomposed in the presence of titanium dioxide which was also added.…”
Section: Carcinogenic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Nevertheless, these alternative plasticizers are still small molecular compounds and migration of plasticizers from soft PVC is unavoidable during long-time service, which would result in decreasing of durability. Several strategies have been developed to reduce migration of small molecular plasticizers from flexible PVC, including surface crosslinking, [12][13][14] surface grafting, [15][16][17][18] surface coating, [19][20][21][22][23] coextrusion, 24,25 mixing with nano-particles, [26][27][28][29][30] internal plasticization, [31][32][33] blending, [34][35][36][37][38][39][40][41] and so forth. Blending with macromolecular plasticizers is one of the few solutions which combines practicability with effectiveness, due to its ease of manufacturing and nonmigratory nature of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A major point of concern with monomeric plasticizers in particular in packaging applications is the loss of the plasticizer due to migration, extraction, or evaporation . As a consequence, polymeric or oligomeric plasticizers became increasingly attractive in recent years because of the reduced loss due to their higher molecular weights . Widely used are polyethylene glycols (PEG) and polyesters .…”
Section: Introductionmentioning
confidence: 99%